1999
DOI: 10.1088/0953-8984/11/20/101
|View full text |Cite
|
Sign up to set email alerts
|

Observation of defects in a C3N4/diamond/Si structure by infrared light scattering tomography

Abstract: A structure of C3N4 and diamond multilayers on Si(100) substrate was prepared by plasma enhanced chemical vapour deposition and magnetron sputtering techniques. Morphology observation and chemical composition analysis of the structure were performed by scanning electron microscopy and energy dispersive x-ray analysis. The multilayers of C3N4 and diamond on Si substrate were clearly observed and the composition ratio of nitrogen to carbon was close to 1.33. Defects in this structure were, for the first time, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nitrogen doping enhances the thermionic electron emission (TEE) and electron field emission (EFE) properties of diamond films . In the past, several groups have attempted to incorporate nitrogen into diamond in large quantities, with the aim of forming the long sought β‐C 3 N 4 phase . Strother et al reported amine terminated diamond surfaces for anchoring organic molecules by photochemical reactions, which generated an interest in chemical sensing applications of diamond terminated with nitrogen functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen doping enhances the thermionic electron emission (TEE) and electron field emission (EFE) properties of diamond films . In the past, several groups have attempted to incorporate nitrogen into diamond in large quantities, with the aim of forming the long sought β‐C 3 N 4 phase . Strother et al reported amine terminated diamond surfaces for anchoring organic molecules by photochemical reactions, which generated an interest in chemical sensing applications of diamond terminated with nitrogen functional groups.…”
Section: Introductionmentioning
confidence: 99%